2016
DOI: 10.1039/c6ra04860a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of polyimides containing hexaisobutyl-substituted T8 cages in their main chains

Abstract: We prepared two types of polyimides containing T8 cages in the main chains by polymerization of para-substituted bis(3-aminopropyl)hexaisobutyl-substituted T8 cage, and studied their mechanical, thermal, and optical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Caged polysilsesquioxane is a good choice for the preparation of transparent PI with high T g due to its large space volume and excellent thermal stability. Maegawa et al 124 used bis(3‐aminopropyl)hexaisobutyl‐substituted T 8 (Figure 10a) containing a cage polysilsesquioxane to polymerize with 6FDA and PMDA, respectively. PI T8 ‐6FDA is colorless and transparent, with its λ 0 319 nm and T 360 greater than 80% (100 μm).…”
Section: Transparent Pi With High Tgmentioning
confidence: 99%
“…Caged polysilsesquioxane is a good choice for the preparation of transparent PI with high T g due to its large space volume and excellent thermal stability. Maegawa et al 124 used bis(3‐aminopropyl)hexaisobutyl‐substituted T 8 (Figure 10a) containing a cage polysilsesquioxane to polymerize with 6FDA and PMDA, respectively. PI T8 ‐6FDA is colorless and transparent, with its λ 0 319 nm and T 360 greater than 80% (100 μm).…”
Section: Transparent Pi With High Tgmentioning
confidence: 99%
“…The materials are known for their well-defined structures containing rigidly inorganic cores with organic substituents in the peripheral. [8][9][10][11][12][13] Several types of POSS-based polymers have been prepared, including main-chain types from bifunctional POSS monomers [13][14][15][16][17][18][19] and network types from octa-functional POSSs. [20][21][22][23][24] However, POSSs for the former category are limited to certain organic substituents on their peripheral, while it is difficult to control the crosslinking of the latter type.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that para ‐bis(3‐aminopropyl)hexaisobutyl‐substituted T 8 cage ( bis‐T 8 ) was successfully synthesized . Incorporation of the T 8 unit in the main chain significantly improves hydrophobicity as well as increasing their glass transition temperatures …”
Section: Introductionmentioning
confidence: 99%
“…13 Incorporation of the T 8 unit in the main chain significantly improves hydrophobicity as well as increasing their glass transition temperatures. 14,15 Here, we first time prepared main-chain type POSS containing coordination polymers. Transition metal complexes with Schiff base ligands are promising materials for optoelectronic applications and the ease of synthesis that readily allows structural modification for optimization of material properties.…”
mentioning
confidence: 99%